FACTORS INFLUENCING STUDENTS’ CHOICE OF ACCOUNTING AS A MAJOR IN PEKANBARU CITY - Evangeline, Justine; Lukman, Hendro (International Journal of Application on Economics and Business, 2024)
There has been a decline in the intention of High School students in choosing accounting as a further study recently, including in Indonesia. High school students tend to think that the field of accounting has no future and will be replaced so that their intention in entering the field of accounting decreases. This research wants to analyze the variables of Personal Characteristics, Career Perceptions, and Social Environment on Students' Intention in choosing an accounting major. The research chose students in Pekanbaru City as subjects. The research uses primary data by distributing digital questionnaires. Data collection methods use the Convenience and Snow-ball methods. Data was collected from 110 respondents and analyzed by multiple regression. The research results show that career perception does not influence students' intention in choosing an accounting major, while personal characteristics and social environment variables influence the intention of High School students in choosing accounting as a further study in university. The implication of this research is that the role of schools and universities should be clearer about accounting major. Schools and universities should convey that accounting careers are still attractive and definitely needed in the business world so that high school students can change their characteristics in choosing an accounting major.